Time and eternity. Regarding the analysis of time on book XI of Augustine’s Confessions - Carrillo Castillo, Lucy (Estudios de Filosofía, 2002)
It is not nonsense to say that for the bishop of Hipona, just as for the neo-platonics, time is the image of eternity. However, that relation, time-eternity, has a particular significance for Augustine. Augustine seeks to prove in books from XI to XIII of the Confessions, that the book of Genesis is the Christians’ Timaeus. In view of the first lines of the book of Genesis, these last three books of the Confessions have the task to reach understanding of the origin of the universe, that shows how eternal continuously acts upon temporary, in such a way that Augustine could found his dogma of salvation within a time- eternity relation. Here, the author follows the course of the reflections in book XI of Confessions, to finally point out, both Augustinian condemnation of the temporary and also the problematicity of the concept of eternity.